2017
DOI: 10.1111/dom.12917
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 inhibitors and risk of adverse renal outcomes among patients with type 2 diabetes: A network and cumulative meta‐analysis of randomized controlled trials

Abstract: Aim:To compare the associations of individual sodium-glucose co-transporter-2 (SGLT2) inhibitors with adverse renal outcomes in patients with type 2 diabetes mellitus (T2DM).Methods: PubMed, EMBASE, CENTRAL and ClinicalTrials.gov were searched for studies published up to May 24, 2016, without language or date restrictions. Randomized trials that reported at least 1 renal-related adverse outcome in patients with T2DM treated with SGLT2 inhibitors were included. Pairwise and network meta-analyses were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 44 publications
2
46
1
Order By: Relevance
“…8 Empagliflozin was significantly associated with a lower risk of composite renal events (OR 0.72, 95% CI 0.60-0.86), an effect which was largely driven by the EMPA-REG study. 8 Finally, a meta-analysis of five trials comprising 13 510 patients revealed lower rates of AKI with SGLT2-i versus controls (OR 0.80, 95% CI 0.67-0.96). 9 An observational study which included users of SGLT2-i versus non-users in two large cohorts did not find an increased risk of AKI in the inpatient setting with SGLT2-i.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…8 Empagliflozin was significantly associated with a lower risk of composite renal events (OR 0.72, 95% CI 0.60-0.86), an effect which was largely driven by the EMPA-REG study. 8 Finally, a meta-analysis of five trials comprising 13 510 patients revealed lower rates of AKI with SGLT2-i versus controls (OR 0.80, 95% CI 0.67-0.96). 9 An observational study which included users of SGLT2-i versus non-users in two large cohorts did not find an increased risk of AKI in the inpatient setting with SGLT2-i.…”
Section: Discussionmentioning
confidence: 95%
“…The rates of events consistent with decreased renal function were 2.2, 1.8 and 1.8 per 100 patient‐years in subjects assigned to placebo, empagliflozin 10 mg and empagliflozin 25 mg, respectively . A meta‐analysis of over 50 randomized controlled trials with SGLT2‐i showed an increased risk of composite renal events (which included events of increased creatinine levels) with dapagliflozin and canagliflozin compared with placebo, yet there was no increased risk of AKI with any of the SGLT2‐i . Empagliflozin was significantly associated with a lower risk of composite renal events (OR 0.72, 95% CI 0.60‐0.86), an effect which was largely driven by the EMPA‐REG study .…”
Section: Discussionmentioning
confidence: 98%
“…The authors concluded that, among the 3 currently approved SGLT2 inhibitors, dapagliflozin and canagliflozin may be associated with an increased risk of harmful renal outcomes, while empagliflozin may provide benefits with regard to renal function. 1 The authors supported this conclusion based on the Drug Safety Communication from the US Food and Drug Administration (FDA) that strengthened existing warnings about the risk of acute kidney injury for canagliflozin and dapagliflozin in June 2016. 2 Unfortunately, the article does not mention the inclusion of empagliflozin in the December 2015 tracked safety notification on acute kidney injury with SGLT2 inhibitors 3 or the acute kidney injury warning in the empagliflozin US prescribing information dated December 2016.…”
mentioning
confidence: 96%
“…In a recent article, Tang et al 1 described the effects of sodium glucose co-transporter 2 (SGLT2) inhibitors on renal outcomes in patients with type 2 diabetes mellitus (T2DM) based on a metaanalysis of data from randomized controlled clinical trials. The authors concluded that, among the 3 currently approved SGLT2 inhibitors, dapagliflozin and canagliflozin may be associated with an increased risk of harmful renal outcomes, while empagliflozin may provide benefits with regard to renal function.…”
mentioning
confidence: 99%
“…A meta-analysis of SGLT2 inhibitor therapy focus on renal safety involved in more than 30,000 patients showed that a total of 511 events of acute renal impairment/failure were reported in 53 trials, revealed that Canagliflozin (OR, 1.82; 95% CI, 0.28 to 11.77) and Dapagliflozin (OR, 1.64; 95% CI, 1.26 to 2.13) had a tendency to increase the adverse renal events as compared with control group, while only Empagliflozin in those three compounds was significantly associated with lower risk of acute renal impairment/failure events than placebo (OR, 0.72; 95% CI, 0.59 to 0.87) [23]. …”
mentioning
confidence: 99%